Composite material and preparation method thereof, luminescent device and display device
By lighting the N-type metal oxides with the first metal salt, the composite composite material with a high-level energy-level-level high-level level is formed to solve the challenge of the N-type semiconductor material in terms of electronic injection performance regulation. Balanced and luminous devices are prolonged.
Patent Information
- Application Number
- CN202310935444.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-27
- Publication Date
- 2025-01-28
AI Technical Summary
Existing N-type semiconductor materials have challenges in regulating electron injection performance, and it is difficult to effectively regulate electron injection performance.
By providing a preparation method for composite materials, including the light treatment of N -type metal oxides with the first metal salt to form the first metal oxide. As a result, electrons are blocked and inhibited electron injection.
This method can effectively regulate electronic injection performance, improve the injecting balance of electronic-cave, and extend the life of the luminous devices.
Smart Images

Figure CN119384155A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of display technology, and in particular to a composite material and a preparation method thereof, a light-emitting device and a display apparatus. Background Art
[0002] There are two types of carriers in semiconductor materials, holes in the valence band and electrons in the conduction band. According to the difference in the concentration of electrons and holes in semiconductor materials, they are divided into N-type semiconductor materials and P-type semiconductor materials. Among them, N-type semiconductor materials are also called electron-type semiconductors, which are impurity semiconductors with a free electron concentration much greater than the hole concentration. P-type semiconductor materials are also called hole-type semiconductors, which are semiconductors that mainly conduct electricity with positively charged holes, or impurity semiconductors with a hole concentration much greater than the free electron concentration.
[0003] N-type semiconductor materials are widely used as electron transport and injection materials due to their good electron injection performance, but how to regulate their electron injection performance has become a key issue in their application. Summary of the invention
[0004] In view of this, the present application provides a composite material and a preparation method thereof, a light-emitting device and a display device, aiming to provide a composite material to regulate electron injection performance.
[0005] The embodiment of the present application is implemented as follows:
[0006] In a first aspect, an embodiment of the present application also provides a method for preparing a composite material, comprising: providing a first mixture, wherein the first mixture comprises an n-type metal oxide and a solvent; after subjecting the first mixture to a first light treatment, adding a first metal salt to the first mixture, and continuing the second light treatment to obtain a composite material; wherein the conduction band energy level of the first metal oxide prepared from the first metal salt is 0.2 to 0.5 eV higher than the conduction band energy level of the n-type metal oxide.
[0007] In a second aspect, the present application also provides a composite material prepared by the above-mentioned composite material preparation method; and / or the composite material comprises an n-type metal oxide doped with a first transition metal oxide, wherein the conduction band energy level of the first transition metal oxide is 0.2 to 0.5 eV higher than the conduction band energy level of the n-type metal oxide.
[0008] In a third aspect, an embodiment of the present application further provides a light-emitting device, comprising: a first electrode and a second electrode arranged opposite to each other; a light-emitting layer arranged between the first electrode and the second electrode; an electronic functional layer arranged between the second electrode and the light-emitting layer; wherein the material of the electronic functional layer comprises the above-mentioned composite material, or comprises a composite material obtained by the preparation method of the above-mentioned composite material.
[0009] In a fourth aspect, an embodiment of the present application further provides a display device, comprising a light-emitting device as described above, or comprising a light-emitting device prepared by the above-mentioned preparation method.
[0010] The preparation method of the composite material provided in the present application comprises providing a first mixture, wherein the first mixture comprises an n-type metal oxide and a solvent; after subjecting the first mixture to a first light treatment, a first metal salt is added to the first mixture, and the second light treatment is continued to be performed to obtain a composite material; wherein the conduction band energy level of the first metal oxide prepared from the first metal salt is 0.2 to 0.5 eV higher than the conduction band energy level of the n-type metal oxide, and the obtained composite material can produce a certain degree of blocking to electrons, inhibit the injection of electrons to a certain extent, and delay the injection efficiency of electrons. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0012] Figure 1 It is a schematic flow chart of an embodiment of a method for preparing a composite material provided in the present application;
[0013] Figure 2 A structural schematic diagram of an embodiment of a light emitting device is provided for the present application.
[0014] Figure 3 A schematic diagram of a process of an embodiment of a method for preparing a light-emitting device provided in the present application;
[0015] Figure 4 A schematic diagram of another embodiment of a method for preparing a light-emitting device provided in the present application;
[0016] Figure 5 and Figure 6 AFM images of the electron transport layer in device comparative example 1 and device embodiment 2 respectively;
[0017] Figure 7 and Figure 8 The hydrated particle size distribution diagrams corresponding to Example 1 and Example 2 respectively;
[0018] Figure 9a and Figure 9b JV curves of single electron devices corresponding to device embodiments 1-16 and device comparative examples 1-2;
[0019] Fig.10a and Fig.10b 1-16 and 1-2 are operating voltage curves of single electron devices corresponding to device embodiments 1-16 and device comparative examples 1-2;
[0020] Fig.11 and Fig.12 Conduction band position diagrams of zinc magnesium oxide and cobalt oxide respectively.
[0021] Reference numerals: light emitting device 100 ; first electrode 10 ; second electrode 20 ; light emitting layer 30 ; electron functional layer 40 , electron injection layer 41 , electron transport layer 42 ; hole functional layer 50 , hole injection layer 51 , hole transport layer 52 . DETAILED DESCRIPTION
[0022] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application. In the present application, unless otherwise specified, the directional words such as "upper" and "lower" used are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may exist in the form of a range; it should be understood that the description in the form of a range is only for convenience and simplicity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single values within the range. For example, description of a range from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the stated range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited numeral (fractional or integral) within the stated range.
[0023] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.
[0024] In the present application, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0025] In the present application, "ring atoms" means the number of atoms of the ring atoms constituting the ring itself in a structural compound (e.g., a monocyclic compound, a condensed ring compound, a cross-linked compound, a carbocyclic compound, a heterocyclic compound) formed by atoms bonding to form a ring, i.e., the number of atoms forming the ring. When the ring is substituted by a substituent, the atoms contained in the substituent are not included in the ring atoms. The same is true for the "ring atoms" described below, unless otherwise specified. For example, the number of ring atoms of a benzene ring is 6, the number of ring atoms of a naphthalene ring is 10, and the number of ring atoms of a thienyl group is 5.
[0026] In the present application, "aryl or aromatic group" refers to an aromatic hydrocarbon group derived from an aromatic ring compound by removing a hydrogen atom, which can be a monocyclic aromatic group, a condensed aromatic group, or a polycyclic aromatic group. For polycyclic rings, at least one is an aromatic ring system. For example, "aryl having 5-30 ring atoms" refers to an aromatic group containing 6 to 30 ring atoms, and the aromatic group can be optionally further substituted. Preferably, substituted or unsubstituted aromatic groups having 6 to 24 ring atoms are used, more preferably substituted or unsubstituted aromatic groups having 6 to 18 ring atoms are used, and particularly preferably substituted or unsubstituted aromatic groups having 6 to 14 ring atoms are used, and the aromatic group can be optionally further substituted; suitable examples include, but are not limited to, phenyl, biphenyl, terphenyl, naphthyl, anthracenyl, phenanthrenyl, fluoranthenyl, triphenylene, pyrenyl, perylene, naphthyl, fluorenyl, dinaphthylenyl, acenaphthene and derivatives thereof. It is understandable that multiple aromatic groups may also be interrupted by short non-aromatic units (e.g. <10% non-H atoms, such as C, N or O atoms), specifically acenaphthene, fluorene, or 9,9-diarylfluorene, triarylamine, diaryl ether systems should also be included in the definition of aromatic groups.
[0027] In the present application, "heteroaryl or heteroaromatic group" means that at least one carbon atom is replaced by a non-carbon atom on the basis of an aromatic group, and the non-carbon atom can be an N atom, an O atom, an S atom, an Si atom, a P atom, etc. For example, "heteroaryl having 5-30 ring atoms" means a heteroaryl having 5 to 30 ring atoms, preferably a substituted or unsubstituted heteroaryl having 5 to 24 ring atoms, more preferably a substituted or unsubstituted heteroaryl having 5 to 18 ring atoms, and particularly preferably a substituted or unsubstituted heteroaryl having 5 to 14 ring atoms, and the heteroaryl is optionally further substituted; suitable examples include, but are not limited to: thienyl, furanyl, pyrrolyl, oxadiazolyl, triazolyl, imidazolyl, pyridyl, bipyridyl, pyrimidyl, triazinyl, Acridinyl, pyridazinyl, pyrazinyl, quinolyl, isoquinolyl, quinazolinyl, quinoxalinyl, phthalazinyl, pyridopyrimidinyl, pyridopyrazinyl, benzothienyl, benzofuranyl, indolyl, pyrroloimidazolyl, pyrrolopyrrolyl, thienopyrrolyl, thienothiphenyl, furopyrrolyl, furofuranyl, thienofuranyl, benzisoxazolyl, benzisothiazolyl, benzimidazolyl, o-naphthyl, phenanthridinyl, primary pyridyl, quinazolinone, dibenzothienyl, dibenzofuranyl, carbazolyl and derivatives thereof.
[0028] The present application provides a composite material, comprising an n-type metal oxide doped with a first metal oxide, wherein the conduction band energy level of the first metal oxide is 0.2 to 0.5 eV greater than the conduction band energy level of the n-type metal oxide.
[0029] In this embodiment, the conduction band energy level of the first metal oxide is 0.2 to 0.5 eV greater than the conduction band energy level of the n-type metal oxide, which can block the electrons to a certain extent, inhibit the injection of electrons to a certain extent, and delay the injection efficiency of electrons. When the composite material is used in a light-emitting device, it can improve the injection balance of electrons and increase the life of the light-emitting device.
[0030] In this embodiment, the n-type metal oxide belongs to an n-type semiconductor material, which is a semiconductor material that is mainly electronically conductive. That is, there are two types of carriers in the n-type metal oxide, namely, holes in the valence band and electrons in the conduction band, but electronic conductivity is the main one.
[0031] In one embodiment, the n-type metal oxide includes a doped or undoped second metal oxide, the undoped second metal oxide includes one or more of zinc oxide, titanium dioxide, and tin dioxide, the doped second metal oxide includes the undoped second metal oxide and a doping element, and the doping element includes one or more of Mg, Ca, Li, Ga, Al, Co, Zr, W, Ti, and Y.
[0032] In one embodiment, the n-type metal oxide is selected from zinc oxide. In another embodiment, the n-type metal oxide is selected from Mg-doped zinc oxide (ZMO).
[0033] In one embodiment, the first metal oxide includes one or more of copper oxide, manganese oxide, and chromium oxide.
[0034] In a specific embodiment, the n-type metal oxide is selected from zinc oxide or doped zinc oxide, and the first metal oxide is selected from copper oxide. In this specific embodiment, copper oxide doped zinc oxide has a 2+ Radius (0.074nm) and Zn 2+ The radius (0.072nm) is similar, Cu 2+ It is easy to fill the Zn vacancies of zinc oxide, thereby reducing the defects of zinc oxide nanoparticles. In addition, the conductivity of copper oxide is relatively poor, which can reduce the conductivity of the composite material and slow down the injection rate of electrons.
[0035] In this embodiment, the group is coordinated and connected to the surface of the n-type metal oxide. On the one hand, it can combine with a large number of oxygen defects on the surface of the n-type metal oxide to increase the dispersibility of the n-type metal oxide and improve the film-forming property of the composite material; on the other hand, it can effectively confine electrons in the composite material to reduce electron injection.
[0036] In one embodiment, the group is selected from one or more of the following structural formulas:
[0037]
[0038] Wherein, each occurrence of R1, R2, R3, and R4 is independently selected from one or more of H, D, -NH2, C1-C30 alkyl, aryl having 5-30 ring atoms, heteroaryl having 5-30 ring atoms, and C1-C30 alkyl substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, aryl having 5-30 ring atoms substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, and heteroaryl having 5-30 ring atoms substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl.
[0039] Wherein, X is a halogen, selected from one or more of F, Cl, Br, and I.
[0040] It can be understood that the number of carbon atoms in the C1-C30 alkyl, the aryl having 5-30 ring atoms, and the alkyl, aryl or heteroaryl in the heteroaryl having 5-30 ring atoms can be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, or 30.
[0041] It can be understood that the aromatic group having 5-30 ring atoms substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl specifically means that the H on the aromatic group having 5-30 ring atoms can be replaced by one or more of hydroxyl, -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl.
[0042] Further, in one embodiment, each occurrence of R1, R2, R3, and R4 is independently selected from -NH2, C1-C10 alkyl, C1-C10 alkyl substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, and aryl having 5-24 ring atoms substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl.
[0043] The aromatic group having 5 to 24 ring atoms can be selected from one or more combinations of phenyl, naphthyl, biphenyl, pyridyl, pyrimidyl and the like.
[0044] Furthermore, the C1-C10 alkyl group may be selected from one or more of methyl, ethyl, n-propyl, isopropyl, n-butyl and the like.
[0045] In a specific embodiment, each occurrence of R1, R2, R3, and R4 is independently selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, phenyl, naphthyl, biphenyl, pyridyl, benzopyridyl, pyrimidyl, benzopyrimidyl, amino, and one or more of methyl, ethyl, n-propyl, isopropyl, n-butyl, phenyl, naphthyl, biphenyl, pyridyl, and pyrimidyl substituted with at least one of -OH, -X, methyl, ethyl, n-propyl, isopropyl, and n-butyl; X is halogen selected from one or more of F, Cl, Br, and I.
[0046] In one embodiment, R1 is selected from one or more of -NH2, -CH3, -CH2CH3, -CH2F, -CHF2, -CF3, phenyl, naphthyl, biphenyl, tolyl;
[0047] In one embodiment, R2, R3, and R4 are independently selected from one or more of -CH3, -CH2CH3, -CH2F, -CHF2, -CF3, phenyl, naphthyl, biphenyl, and tolyl.
[0048] In one embodiment, each occurrence of R1, R2, R3, and R4 is independently selected from the following groups:
[0049]
[0050] In the present application, "*" indicates a connection site or a fusion site. When the connection site is not specified in the group, it means that an optional connection site in the group is used as the connection site. When the fusion site is not specified in the group, it means that an optional fusion site in the group is used as the fusion site.
[0051] In one embodiment, the organic group may include one or more of the following structural formulas:
[0052]
[0053] The above-mentioned group is electronegative and can be coordinated and connected to the surface of the n-type metal oxide, so that it can combine with a large number of oxygen defects on the surface of the n-type metal oxide, increase the dispersibility of the n-type metal oxide, improve the film-forming property of the composite material, and effectively confine electrons in the composite material to reduce electron injection.
[0054] In one embodiment, the average particle size of the n-type metal oxide is in the range of 3 to 10 nm, specifically 3 to 5 nm, 5 to 10 nm, 3 to 8 nm, 5 to 8 nm, 8 to 10 nm, etc. In one embodiment, the average particle size of the first metal oxide is in the range of 2 to 5 nm, specifically 2 to 3 nm, 3 to 4 nm, 4 to 5 nm, etc. In one embodiment, the mass ratio of the first metal oxide to the n-type metal oxide is (3 to 8): 100, specifically (3 to 7): 100, (4 to 7): 100, (4 to 6): 100, (5 to 6): 100, etc. The mass ratio can reduce the electron injection and transport properties of the composite material to a certain extent, and improve the film forming property.
[0055] The present application also provides a method for preparing a composite material, see Figure 1 , Figure 1It is a flow chart of an embodiment of a method for preparing a composite material provided in the present application, which specifically includes the following steps: Step S11: providing a first mixture, wherein the first mixture includes an n-type metal oxide and a solvent; Step S12: after subjecting the first mixture to a first light treatment, adding a first metal salt to the first mixture, and continuing the second light treatment to obtain a composite material; wherein the conduction band energy level of the first metal oxide corresponding to the first metal salt is 0.2 to 0.5 eV greater than the conduction band energy level of the n-type metal oxide.
[0056] In this embodiment, the first mixture is subjected to a first light irradiation treatment, and under the light irradiation, the n-type metal oxide can excite electrons (e - ), the electrons can react with the oxygen and water in the first mixture system to generate hydroxide, and after the first metal salt is added to the system, the first metal cation in the first metal salt can react with the hydroxide to generate the first metal oxide, and the second light treatment is continued, which can continuously promote the generation of electrons and improve the efficiency of the photocatalytic reaction. The method of this embodiment can generate the first metal oxide in situ. The reaction mechanism can be referred to as follows:
[0057]
[0058] O2+2H2O+4c - →4OH-
[0059]
[0060] In this embodiment, the first metal oxide formed by the first metal salt has a conduction band energy level 0.2 to 0.5 eV higher than that of the n-type metal oxide, which can block electrons to a certain extent, inhibit the injection of electrons to a certain extent, and delay the injection efficiency of electrons. When the composite material is used in a light-emitting device, it can improve the injection balance of electrons and increase the life of the light-emitting device.
[0061] In the step S11:
[0062] The n-type metal oxide may refer to the related description of the composite material mentioned above, which will not be described in detail here.
[0063] In one embodiment, the concentration of the n-type metal oxide in the first mixture is 35-60 mg / mL, specifically 35 mg / mL, 40 mg / mL, 45 mg / mL, 50 mg / mL, 55 mg / mL, 60 mg / mL, etc.
[0064] The solvent includes one or more of an alcohol solvent, an ether solvent, tetrahydrofuran, acetone, chlorobenzene, toluene, etc. Specifically, the alcohol solvent includes one or more of methanol, ethanol, ethylene glycol, isopropanol, n-butanol, etc. The ether solvent includes one or more of methyl ether, ethyl ether, etc.
[0065] In one embodiment, before providing the first mixture, the method further includes: preparing an n-type metal oxide, specifically including the following steps: step S111: dissolving an n-type metal salt in a fourth solvent to obtain an n-type metal salt precursor solution; and dispersing a base in a fifth solvent to obtain an alkaline solution; step S112: adding the alkaline solution to the n-type metal salt precursor solution and stirring to obtain an n-type metal oxide.
[0066] In the step S111: the n-type metal salt is set accordingly according to the specific type of the n-type metal oxide.
[0067] In a specific embodiment, the n-type metal oxide is zinc oxide, and the n-type metal salt is a zinc salt. Specifically, the zinc salt can be selected from one or more of zinc acetate, zinc chloride, zinc bromide, zinc sulfate, zinc carbonate, zinc phosphate, zinc borate and zinc molybdate. In another specific embodiment, the n-type metal oxide is magnesium-doped zinc oxide, and the n-type metal salt includes a zinc salt and a magnesium salt. The molar ratio of the magnesium salt to the zinc salt can be (0.05-5):100, specifically (0.05-1):100, (1-2):100, (2-3):100, (3-4):100, (4-5):100, etc. In other specific embodiments, the n-type metal oxide can be lithium-doped zinc oxide, aluminum-doped zinc oxide, etc. In one embodiment, the concentration of the n-type metal salt in the n-type metal salt precursor solution may be 0.15M to 2M, specifically 0.15M to 0.5M, 0.5M to 1M, 1M to 1.5M, 1.5M to 2M, etc. In one embodiment, the fourth solvent may include one or more of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, tetrahydrofuran or diethyl ether.
[0068] In one embodiment, the concentration of the alkali solution may be 0.08-0.2M, specifically 0.08-0.1M, 0.1-0.12M, 0.12-0.15M, 0.15-0.18M, 0.18-0.2M, etc. In one embodiment, the alkali may be selected from one or more of potassium hydroxide, lithium hydroxide, sodium hydroxide, ammonium hydroxide, ethylenediamine, ethanolamine, diethanolamine, triethanolamine, tetraalkylammonium hydroxide (TAAOH, alkyl = methyl, ethyl, propyl, butyl); in one embodiment, the fifth solvent may include one or more of methanol, ethanol, propanol, butanol, ethylene glycol, isopropanol, glycerol, etc.
[0069] In the step S112: In one embodiment, an alkali solution is added to the n-type metal salt precursor solution to control the system pH to be 11 to 13. In one embodiment, the stirring time may be 1 to 3 hours, specifically 1 to 1.5 hours, 1.5 to 2 hours, 2 to 2.5 hours, 2.5 to 3 hours, etc. In one embodiment, after the stirring, the mixed system may be precipitated in excess ethyl acetate or acetone, and the supernatant may be removed and centrifuged to obtain the n-type metal oxide.
[0070] In the step S12: In one embodiment, the first metal salt includes an anion and a first metal cation. Specifically, the anion can refer to the relevant description of the group described above, which will not be repeated here.
[0071] In this embodiment, the anions can be connected to the surface of the n-type metal oxide. On the one hand, they can combine with a large number of oxygen defects on the surface of the n-type metal oxide, which can effectively avoid the regrowth and agglomeration of n-type metal oxide nanoparticles and improve the uniformity and film-forming properties of the particles in the composite material; on the other hand, they can effectively confine electrons in the composite material and reduce electron injection.
[0072] In addition, during the light treatment process, the holes (h+) generated by photocatalysis can effectively fill the defects on the surface of the n-type metal oxide (such as oxygen vacancies, etc.), play a role in passivating the n-type metal oxide, and can effectively avoid the regrowth of n-type metal oxide nanoparticles, improve the uniformity of the particles in the composite material, reduce agglomeration, and thus improve the film-forming property of the composite material.
[0073] In one embodiment, the first metal cation may include a copper ion (Cu 2+ ), manganese ion (Mn 2+ ), chromium ion (Cr 3+ ). In a specific embodiment, the first metal salt includes an organic copper salt, which may specifically include one or more of trifluoromethanesulfonate copper (II), methanesulfonate copper (II), trifluoroacetylacetonate copper (II), bis (trifluoromethanesulfonyl) imide copper (II), acetylacetonate copper (II), tetrafluoroborate copper (II), etc. Wherein "II" indicates that the valence state of copper is +2. In a specific embodiment, the first metal salt includes an organic manganese salt, which may specifically include one or more of trifluoromethanesulfonate manganese (II), bis (trifluoromethanesulfonyl) imide manganese (II), etc. Wherein "II" indicates that the valence state of manganese is +2. In a specific embodiment, the first metal salt includes an organic chromium salt, which may specifically include one or more of methanesulfonate chromium (III), benzoyl acetonate chromium (III), tetrafluoroborate chromium (III), etc. Wherein "III" indicates that the valence state of chromium is +3.
[0074] In one embodiment, a first metal salt is added to the first mixture, wherein the mass ratio of the first metal salt to the n-type metal oxide is (1-2):20, i.e., (5-10):100, and specifically can be (5-9):100, (6-9):100, (6-8):100, (7-8):100, (5-6):100, (9-10):100, etc. The mass ratio can provide enough of the first metal salt to form the first metal oxide, thereby improving the film-forming property of the composite material, making the composite material include a gradient conduction band energy level, and reducing electron injection. It also provides enough anions to coordinate and connect to the n-type metal oxide, reducing the surface defects of the n-type metal oxide, and improving the film-forming property of the composite material.
[0075] In one embodiment, the first mixture further includes a hole sacrificial agent, which can consume holes generated by photocatalysis, thereby providing more electrons to generate hydroxide.
[0076] Furthermore, the hole sacrificial agent may include one or more of acetonitrile, triethylamine, triethanolamine, sodium sulfite, methanol, ethanol, lactic acid, and the like.
[0077] In one embodiment, the mass ratio of the hole sacrificial agent to the n-type metal oxide may be (0.5-1.5):5, specifically (0.5-1.0):5, (1.0-1.5):5, etc.
[0078] It can be understood that when the solvent included in the first mixture includes methanol, ethanol, etc., the solvent can have the function of a hole sacrificial agent and can consume holes. In this case, there is no need to add the hole sacrificial agent additionally.
[0079] In one embodiment, the first metal salt is added to the first mixture in the form of a solution. Specifically, the second solvent corresponding to the first metal salt may include one or more of water, alcohol solvents, ether solvents, tetrahydrofuran, acetone, chlorobenzene, and toluene. Specifically, the alcohol solvent includes one or more of methanol, ethanol, ethylene glycol, isopropanol, and n-butanol. The ether solvent includes one or more of methyl ether and ethyl ether.
[0080] In one embodiment, the first metal salt is added while the first mixture is in a stirring state to improve the mixing uniformity of the first mixture and the first metal salt, thereby promoting the generation of the first metal oxide.
[0081] In one embodiment, the duration of the first light treatment is 1 to 2 hours, specifically 1 to 1.5 hours, 1.5 to 2 hours, etc.
[0082] In one embodiment, the first light treatment is full-spectrum light treatment, that is, full-band light treatment is used. Specifically, the wavelength range of the first light treatment can be 200-2500nm, such as one or more of 200-380nm, 380-760nm, 760-2500nm, etc.
[0083] In one embodiment, the first light treatment may include one or more of ultraviolet light band (UV for short, wavelength 200-380nm), visible light band (VL for short, wavelength 380-760nm) or infrared light band (IR for short, wavelength 760-2500nm).
[0084] In one embodiment, the light source for the first light treatment may be a single light source or a composite light source formed by multiple light sources. In a specific embodiment, the light source for the first light treatment is a xenon (Xe) lamp. Specifically, the power of the Xe lamp may be 200-500W, such as 200-300W, 300-400W, 400-500W, etc.
[0085] In one embodiment, during the first light irradiation process, the first mixture is in a stirring state to improve mixing uniformity, improve light irradiation uniformity, and improve heat dissipation.
[0086] In one embodiment, during the first light treatment of the first mixture, the temperature of the first mixture is maintained at 0-30°C, such as 0-4°C, 4-20°C, 20-25°C, 25-30°C, etc. Specifically, the first mixture can be protected by circulating condensed water to control the temperature of the first mixture within a preset range to avoid excessive temperature of the first mixture due to heat generation from light.
[0087] The second light irradiation time is 4 to 8 hours, specifically 5 to 8 hours, 5 to 7 hours, 6 to 7 hours, 7 to 8 hours, etc. The second light irradiation time range can photocatalytically obtain a preset loading of the first metal oxide.
[0088] In one embodiment, the second illumination treatment is full-spectrum illumination treatment, that is, full-band illumination is used.
[0089] In one embodiment, the wavelength range of the second light treatment is 200-2500 nm, such as one or more of 200-380 nm, 380-760 nm, 760-2500 nm, etc.
[0090] In one embodiment, the second light treatment may include one or more of ultraviolet light band (UV for short, wavelength 200-380nm), visible light band (VL for short, wavelength 380-760nm) or infrared light band (IR for short, wavelength 760-2500nm).
[0091] In one embodiment, the light source for the second illumination treatment may be a single light source or a composite light source formed by multiple light sources.
[0092] In a specific embodiment, the light source of the second light treatment is a xenon (Xe) lamp. Specifically, the power of the Xe lamp can be 200-500W, such as 200-300W, 300-400W, 400-500W, etc.
[0093] In one embodiment, a first metal salt is added to the first mixture to obtain a second mixture, and a second light treatment is continued. During the second light treatment of the second mixture, the temperature of the second mixture is maintained at 0 to 30° C., such as 0 to 4° C., 4 to 20° C., 20 to 25° C., 25 to 30° C., etc. Specifically, the second mixture can be protected by circulating condensed water to control the temperature of the second mixture within a preset range to avoid excessive temperature of the second mixture due to heat generation from light.
[0094] In one embodiment, the first metal salt is added to the first mixture to obtain the second mixture, and during the second light irradiation treatment, the second mixture can be stirred to improve the mixing uniformity and the rate of generating the first metal oxide.
[0095] In one embodiment, after the second light treatment, the method further includes: using a cleaning agent to perform sedimentation washing on the mixture N times, where N is an integer greater than or equal to 2, such as washing three times. The cleaning agent may include one or more of ethyl acetate and acetone. In this embodiment, unreacted reactants, such as unreacted first metal salt, etc., may be removed by multiple washings.
[0096] The present application also provides a composite material, which is prepared by the above-mentioned preparation method of the composite material.
[0097] The present application provides a light emitting device, referring to Figure 2 , Figure 2 The present application provides a structural schematic diagram of an embodiment of a light-emitting device, wherein the light-emitting device 100 includes a first electrode 10 and a second electrode 20 that are relatively arranged, and a light-emitting layer 30 that is arranged between the first electrode 10 and the second electrode 20, and an electronic functional layer 40 that is arranged between the second electrode 20 and the light-emitting layer 30.
[0098] The material of the electronic functional layer 40 includes the composite material provided in the present application, or includes the composite material prepared by the preparation method of the composite material provided in the present application.
[0099] In the present embodiment, the material of the electronic functional layer 40 includes a composite material, that is, an n-type metal oxide doped with a first metal oxide, wherein the conduction band energy level of the first metal oxide is 0.2 to 0.5 eV greater than the conduction band energy level of the n-type metal oxide, and the first metal oxide forms an electron barrier between the n-type metal oxide and the second electrode 20, thereby effectively blocking electron injection, and the conductivity of copper oxide is relatively poor, which can slow down the injection rate of electrons, thereby effectively improving the electron-hole injection balance, improving the carrier balance of the light-emitting device 100, and avoiding excessive electrons from having a negative impact on the light-emitting layer 30 and the film layer on the hole side, thereby improving the life and light-emitting stability of the light-emitting device 100.
[0100] Furthermore, an organic group having an electron donating function is connected to the n-type metal oxide, which can effectively confine electrons at the interface between the electronic functional layer 40 and the second electrode 20, avoiding the electrons from jumping to the hole side, thereby reducing the probability of the material on the hole side being destroyed, thereby improving the carrier injection balance and life of the light-emitting device 100.
[0101] In addition, the organic group containing the electron-donating group is coordinated and connected to the surface of the n-type metal oxide. On the one hand, it can combine with a large number of oxygen defects on the surface of the n-type metal oxide, which can increase the dispersibility of the n-type metal oxide and improve the film-forming property of the composite material, thereby improving the uniformity and density of the film of the electronic functional layer 40, reducing and avoiding the leakage current phenomenon of the light-emitting device 100, and improving the stability of the light-emitting device 100.
[0102] In one embodiment, the material of the electronic functional layer 40 is composed of a composite material. In other embodiments, the material of the electronic functional layer 40 may include other materials such as metal elements in addition to the composite material.
[0103] In one embodiment, the electronic functional layer 40 may include one or both of an electron injection layer 41 and / or an electron transport layer 42; when the electronic functional layer 40 includes two layers, the electron injection layer 41 and the electron transport layer 42, the electron injection layer 41 is arranged close to the second electrode 20, and the electron transport layer 42 is arranged close to the light-emitting layer 30, and the material of the electron transport layer 42 includes the composite material.
[0104] In one embodiment, in one embodiment, the thickness of the electron transport layer 42 may be 20-40 nm, specifically 20-35 nm, 25-35 nm, 25-30 nm, 20-25 nm, 35-40 nm, etc.
[0105] In one embodiment, the material of the electron injection layer 41 can be a material known in the art for electron injection layer, for example, it can be selected from but not limited to at least one of LiF, MgP, MgF2, Al2O3, Ga2O3, LiF / Yb, ZnO, Cs2CO3, RbBr, and Rb2CO3.
[0106] In one embodiment, the material of the light-emitting layer 30 is selected from organic light-emitting materials or quantum dot light-emitting materials.
[0107] The organic light-emitting material may be selected from at least one of diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives or fluorene derivatives, TBPe fluorescent materials emitting blue light, TTPA fluorescent materials emitting green light, TBRb fluorescent materials emitting orange light, and DBP fluorescent materials emitting red light;
[0108] The quantum dot luminescent material can be selected from at least one of a single structure quantum dot, a core-shell structure quantum dot and a perovskite semiconductor material. The single structure quantum dot is selected from at least one of a II-VI group compound, a IV-VI group compound, a III-V group compound and a I-III-VI group compound. The II-VI group compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdS At least one of dZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compound is selected from SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, Sn At least one of PbTe, SnPbSSe, SnPbSeTe, and SnPbSTe, and the III-V compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb , GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, the I-III-VI group compound is selected from at least one of CuInS, CuInSe and AgInS; the core of the quantum dots of the core-shell structure is selected from any one of the above-mentioned single-structure quantum dots, and the shell material of the quantum dots of the core-shell structure is selected from at least one of CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS and ZnS;
[0109] The perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductors, or organic-inorganic hybrid perovskite semiconductors; the inorganic perovskite semiconductor has a general structural formula of AMX3, wherein A is Cs + ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of the following; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - When n=2, the inorganic metal halide octahedron MX6 4- The metal cation M is located at the center of the halogen octahedron, and the organic amine cation B fills the gap between the octahedrons to form an infinitely extended three-dimensional structure. When n>2, the inorganic metal halide octahedron MX6 connected by the top-sharing method 4- It extends in two dimensions to form a layered structure, with an organic amine cation bilayer (protonated monoamine) or an organic amine cation monolayer (protonated diamine) inserted between the layers, and the organic layer and the inorganic layer overlap to form a stable two-dimensional layered structure.
[0110] In one embodiment, the quantum dot luminescent material includes one or more of red quantum dots, green quantum dots, and blue quantum dots.
[0111] The thickness of the light emitting layer 30 may be 5 to 100 nm, specifically 5 to 15 nm, 15 to 30 nm, 15 to 35 nm, 25 to 35 nm, 25 to 30 nm, 30 to 50 nm, 50 to 100 nm, etc.
[0112] In a specific embodiment, the quantum dots are selected from oily quantum dots, and the surface of the quantum dots is connected with a ligand that is easily soluble in a solvent with low polarity, including at least one of an acid ligand, a thiol ligand, an amine ligand, a (oxygen) phosphine ligand, a phospholipid, a soft phosphine, and polyvinyl pyridine. As a specific embodiment, the acid ligand is at least one of deca-acid, undecylenic acid, tetradecanoic acid, oleic acid, and stearic acid; the thiol ligand is at least one of octadecyl mercaptan, dodecyl mercaptan, and octadecyl mercaptan; the amine ligand includes at least one of oleylamine, octadecylamine, and octadecylamine; the (oxygen) phosphine ligand is at least one of trioctylphosphine and trioctylphosphine oxide.
[0113] In one embodiment, the light emitting device 100 may further include a hole functional layer 50, and the hole functional layer 50 is disposed between the first electrode 10 and the light emitting layer 30. The hole functional layer 50 may include a hole injection layer 51 and / or a hole transport layer 52. When the hole functional layer 50 includes two layers, the hole injection layer 51 and the hole transport layer 52, the hole injection layer 51 is disposed close to the first electrode 10, and the hole transport layer 52 is disposed close to the light emitting layer 30.
[0114] In this embodiment, the material of the electronic functional layer 40 includes a composite material, wherein the first metal oxide forms an electron barrier between the n-type metal oxide and the second electrode 20, which can effectively block electron injection, and the conductivity of copper oxide is relatively poor, which can slow down the injection rate of electrons and prevent excessive electrons from having a negative impact on the material of the hole functional layer 50 and a negative impact on the life of the light-emitting device 100.
[0115] In one embodiment, the thickness of the hole injection layer 51 may be 20-200 nm, specifically 20-150 nm, 80-150 nm, 80-120 nm, etc. The thickness of the hole transport layer 52 may be 30-180 nm, specifically 30-150 nm, 50-150 nm, 50-120 nm, 80-120 nm, 80-100 nm, etc.
[0116] The material of the hole transport layer 52 is selected from arylamine, polyaniline, polypyrrole, poly(p-phenylene vinylene) and its derivatives, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compound, N,N,N',N'-tetraarylbenzidine, PEDOT:PSS and its derivatives, poly(N-vinylcarbazole) (PVK) and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, doped or undoped NiO, MoO3, WO3, V2O5, CrO3, CuO, MoS2, MoSe2, WS3, WS e3, CuS, CuSCN; wherein the aromatic amine is selected from 4,4'-di(9-carbazole)biphenyl (CBP), poly(9,9-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine) (TFB), poly(N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl)benzidine) (poly-TPD), N,N'-di(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine (DNTPD), poly(9,9-dioctylfluorene-co-bis-N,N-phenyl-1,4-phenylenediamine) (PFB), 4,4' ,4"-tri(carbazol-9-yl)triphenylamine (TCATA), 4,4',4"-tri(N-carbazol-9-yl)triphenylamine (TCTA), 4,4',4"-tri(N-3-methylphenyl-N-phenylamino)triphenylamine (m-MTDATA), N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine (α-NPD), N,N'-diphenyl-N,N'-bis(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine (TPD), N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine (TPD), ,4'-diamine (NPB), Spiro-NPB, Spiro-TPD, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro(spiro-TPD), spiro-NPB or one or more thereof; the poly(p-)phenylene vinylene and its derivatives are selected from one or more of poly(phenylene vinylene) (PPV), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene] (MEH-PPV) and poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene] (MOMO-PPV).
[0117] The material of the hole injection layer 51 is a material having hole injection capability, selected from poly(ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS), 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanoquinone-dimethane (F4-TCNQ), 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene (HATCN), copper phthalocyanine (CuPc ), poly(9,9-dioctyl-fluorene-co-N-(4-butylphenyl)-diphenylamine) (TFB), polyarylamine, poly(N-vinylcarbazole), polyaniline, polypyrrole, N,N,N',N'-tetrakis(4-methoxyphenyl)-benzidine (TPD), 4-bis[N-(1-naphthyl)-N-phenyl-amino]biphenyl (α-NPD), 4,4',4"-tris[phenyl(m-tolyl)amino]triphenylamine (m-MTDATA), 4,4',4"-tri(N-carbazolyl)-triphenylamine (TCTA), 1,1-bis[(di-4-tolylamino)phenylcyclohexane (TAPC), 4,4',4"-tri(diphenylamino)triphenylamine (TDATA) doped with F4-TCNQ, p-doped phthalocyanine (e.g., F4-TCNQ-doped zinc phthalocyanine (ZnPc)), F4-TCNQ-doped N,N'-diphenyl-N,N'-di(1-naphthyl)-1,1'-biphenyl-4,4"-diamine (α-NPD), transition metal oxides, transition metal sulfur compounds; wherein the transition metal oxides include one or more of NiO, MoO2, WO3, CuO; the metal sulfur compounds include one or more of MoS2, MoSe2, WS3, WSe3, CuS.
[0118] In one embodiment, the first electrode 10 and the second electrode 20 are independently selected from metal electrodes, carbon electrodes, doped or undoped metal oxide electrodes and composite electrodes; wherein the material of the metal electrode is selected from at least one of Al, Ag, Cu, Mo, Au, Ba, Ca, Ni, Ir and Mg; the material of the carbon electrode is selected from at least one of graphite, carbon nanotubes, graphene and carbon fiber; the material of the doped or undoped metal oxide electrode is selected from ITO, FTO, ATO, AZO, GZO, IZO, MZO, I At least one of TZO, ICO, AMO, SnO2, In2O3, Cd:ZnO, F:SnO2, In:SnO2, and Ga:SnO2; the material of the composite electrode is selected from at least one of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, and ZnS / Al / ZnS. Wherein, " / " represents a stacked structure, for example, the composite electrode AZO / Ag / AZO represents an electrode of a composite structure of three stacked layers consisting of an AZO layer, an Ag layer, and an AZO layer.
[0119] The first electrode 10 and the second electrode 20 form a pair of electrodes. In one embodiment, the first electrode 10 is an anode, and the second electrode 20 is a cathode.
[0120] It is understandable that, in addition to the above-mentioned functional layers, the light-emitting device 100 may also be provided with some functional layers conventionally used in light-emitting devices to help improve the performance of the light-emitting device, such as an electron blocking layer, an electron injection layer, a hole blocking layer and / or an interface modification layer.
[0121] It can be understood that the material and thickness of each layer of the light-emitting device 100 can be set and adjusted accordingly according to the light-emitting requirements of the light-emitting device 100 .
[0122] The light emitting device 100 further includes a substrate (not shown), which may also be referred to as a substrate. The substrate may be a rigid substrate or a flexible substrate. The rigid substrate may be a ceramic material or various glass materials. The flexible substrate may be a substrate formed of materials such as polyimide film (PI) and its derivatives, polyethylene naphthalate (PEN), phosphoenolpyruvic acid (PEP) or diphenylene ether resin. In one embodiment, the material of the substrate includes glass, silicon wafer, polycarbonate, polymethyl methacrylate, polyethylene terephthalate, polyethylene naphthalate, polyamide, polyether sulfone, or a combination thereof.
[0123] It can be understood that the light emitting device 100 can be an upright light emitting device or an inverted light emitting device. When the light emitting device 100 is an upright light emitting device, the substrate is combined with a side of the first electrode 10 away from the light emitting layer 30. When the light emitting device 100 is an inverted light emitting device, the substrate is combined with a side of the second electrode 20 away from the light emitting layer 30.
[0124] It is understood that, in addition to the above-mentioned functional layers, the light-emitting device 100 may also be provided with some functional layers conventionally used in light-emitting devices that help improve the performance of the light-emitting device, such as an electron blocking layer, an electron injection layer, a hole blocking layer and / or an interface modification layer, etc. It is understood that the material and thickness of each layer of the light-emitting device 100 may be set and adjusted accordingly according to the light-emitting requirements of the light-emitting device 100.
[0125] The present application also provides a method for preparing a light emitting device, see Figure 3 , Figure 3 The present invention provides a flow chart of a method for preparing a light-emitting device according to an embodiment of the present invention, which specifically includes the following steps:
[0126] Step S21: providing a preset device, wherein the preset device includes a first electrode and a light-emitting layer;
[0127] Step S22: Arranging electronic functional materials on the preset device to form an electronic functional layer;
[0128] Step S23: forming a second electrode on the electronic functional layer to obtain a light-emitting device.
[0129] The light-emitting device prepared in this embodiment is an upright device.
[0130] In one embodiment, the light-emitting device includes a hole functional layer, and the step S21 specifically includes: providing a prefabricated device, wherein the prefabricated device includes a stacked first electrode, a hole functional layer, and a light-emitting layer.
[0131] See also Figure 4 , Figure 4 This is a flow chart of another embodiment of a method for preparing a light-emitting device provided in the present application. The method for preparing a light-emitting device in this embodiment comprises the following steps:
[0132] Step S31: providing a prefabricated device, wherein the prefabricated device includes a second electrode;
[0133] Step S32: Arranging electronic functional materials on the prefabricated device to form an electronic functional layer;
[0134] Step S33: forming a stacked light-emitting layer and a first electrode on the electronic functional layer to obtain a light-emitting device.
[0135] The light-emitting device prepared in this embodiment is an inverted device.
[0136] In one embodiment, the light-emitting device includes a hole functional layer, and the step S33 specifically includes: forming a stacked light-emitting layer, a hole functional layer and a first electrode on the electronic functional layer.
[0137] In the above two embodiments, the electronic functional material includes the composite material provided in the present application, or includes a composite material obtained by the method for preparing the composite material provided in the present application. For details, please refer to the relevant description above, which will not be repeated here. In a specific embodiment, the electronic functional material is the composite material provided in the present application, or is a composite material obtained by the method for preparing the composite material provided in the present application.
[0138] In one embodiment, in step S22 and step S32, the composite material may be disposed on the prefabricated device by a solution method. Specifically, the solution method may be a spin coating method, a printing method, an inkjet printing method, a doctor blade method, a printing method, a dip-coating method, a soaking method, a spray coating method, a roll coating method, a casting method, a slit coating method, a strip coating method, and the like.
[0139] In a specific embodiment, in step S22 and step S32, the step of arranging the composite material on the preset device to form the electronic functional layer includes: arranging a third mixture on the preset device, wherein the third mixture includes the composite material and a third solvent. Specifically, the third solvent may include an alcohol solvent, specifically one or more of methanol, ethanol, isopropanol, n-butanol, etc.
[0140] Furthermore, the concentration of the composite material in the third mixture may be 20-50 mg / mL, specifically 20-45 mg / mL, 25-45 mg / mL, 25-40 mg / mL, 30-40 mg / mL, 30-35 mg / mL, etc.
[0141] After the third mixture is prepared by the solution method, it is necessary to dry it to remove the third solvent. The drying can be heating drying or vacuum drying. The heating drying temperature can be 60 to 80°C and the time can be 20 to 60 minutes. The vacuum drying pressure is 10 -1 ~10 -2 Pa. Furthermore, the vacuum drying temperature may be room temperature (about 25° C.). In other embodiments, the composite material may be disposed on the prefabricated device by other methods known in the art, such as sputtering.
[0142] In each embodiment of the above preparation method, the electron transport layer, hole functional layer, light-emitting layer, first electrode, second electrode, etc. can refer to the corresponding description of the light-emitting device 100 in the previous text, and will not be repeated here.
[0143] In the light-emitting device provided in the present application, the preparation methods of the first electrode, the second electrode, the light-emitting layer, the hole functional layer, the electron functional layer and other film layers can be implemented by conventional techniques in the art, such as chemical methods or physical methods. Among them, the chemical method includes chemical vapor deposition, continuous ion layer adsorption and reaction method, anodization method, electrolytic deposition method, and coprecipitation method. The physical method includes physical plating method and solution method, among which the physical plating method includes: thermal evaporation coating method, electron beam evaporation coating method, magnetron sputtering method, multi-arc ion plating method, physical vapor deposition method, atomic layer deposition method, pulsed laser deposition method, etc.; the solution method can be spin coating, printing method, inkjet printing method, blade coating method, printing method, dip pulling method, immersion method, spraying method, roll coating method, casting method, slit coating method and strip coating method, etc.
[0144] It is understood that the method for preparing the light-emitting device may further include a packaging step, and the packaging material used for packaging may be selected from at least one of UV glue, metal film, and glass glue. In a specific embodiment, the packaging material may be acrylic resin or epoxy resin. The packaging may be machine packaging or manual packaging, and may be sealed with ultraviolet curing glue. The concentration of oxygen and water in the environment of the packaging step is less than 0.1ppm to ensure the stability of the light-emitting device.
[0145] The present application also relates to a display device, which includes the light-emitting device provided in the present application. The display device can be any electronic product with a display function, including but not limited to smart phones, tablet computers, laptop computers, digital cameras, digital video cameras, smart wearable devices, smart weighing electronic scales, car displays, televisions or e-book readers, wherein the smart wearable device can be, for example, a smart bracelet, a smart watch, a virtual reality (VR) helmet, etc.
[0146] The present application is described in detail below through specific embodiments. The following embodiments are only partial embodiments of the present application and are not limitations of the present application.
[0147] Embodiment 1:
[0148] This embodiment provides a method for preparing a composite material and the prepared composite material, wherein the preparation method specifically comprises the following steps:
[0149] Step 1: dissolving magnesium acetate and zinc acetate in dimethyl sulfoxide to obtain a 0.18M metal salt precursor solution, wherein the molar ratio of magnesium to zinc is 5%; dispersing potassium hydroxide in ethanol to obtain a 0.2M alkali solution.
[0150] Step 2: adding alkaline solution to the metal salt precursor solution, stirring for 2 hours, settling the mixture in excess ethyl acetate or acetone, removing the supernatant and centrifuging, dispersing in an ethanol solution to obtain an ethanol solution of zinc oxide magnesium nanoparticles.
[0151] Step 3: Take 20 mL of the 40 mg / mL zinc oxide magnesium ethanol solution, and irradiate the solution under a 300 W Xe lamp (full spectrum) for 1 hour under the protection of circulating condensed water at 4°C while continuously stirring.
[0152] Step 4: Under continuous illumination, 10 mL of 4.0 mg / mL copper (II) trifluoromethanesulfonate ethanol solution was added dropwise to the solution in step 3, and the irradiation was continued for 4 hours, during which the irradiation was carried out under the protection of circulating condensed water at 4°C. After photodeposition, the above solution was washed three times by precipitation in excess ethyl acetate or acetone to wash away the excess copper salt and obtain a composite material.
[0153] Embodiment 2:
[0154] This example is substantially the same as Example 1, except that in step 4, 10 mL of 6.0 mg / mL copper (II) trifluoromethanesulfonate ethanol solution is added.
[0155] Embodiment 3:
[0156] This example is substantially the same as Example 1, except that in step 4, 10 mL of 8.0 mg / mL copper (II) trifluoromethanesulfonate ethanol solution is added.
[0157] Embodiment 4:
[0158] This example is basically the same as Example 1, except that in step 4, 10 mL of 6.0 mg / mL methanesulfonate copper (II) ethanol solution is added.
[0159] Embodiment 5:
[0160] This example is substantially the same as Example 1, except that in step 4, 10 mL of 6.0 mg / mL trifluoroacetylacetonate copper (II) ethanol solution is added.
[0161] Embodiment 6:
[0162] This example is substantially the same as Example 1, except that in step 4, 10 mL of 6.0 mg / mL bis(trifluoromethanesulfonyl)imide copper (II) solution is added.
[0163] Embodiment 7:
[0164] This example is substantially the same as Example 1, except that in step 4, 10 mL of 6.0 mg / mL acetylacetonate copper (II) ethanol solution is added, and irradiation is continued for 8 hours.
[0165] Embodiment 8:
[0166] This example is substantially the same as Example 1, except that in step 4, 10 mL of 6.0 mg / mL copper (II) tetrafluoroborate ethanol solution is added, and irradiation is continued for 6 hours.
[0167] Embodiment 9:
[0168] This example is substantially the same as Example 1, except that in step 4, 10 mL of a 2.5 mg / mL copper trifluoromethanesulfonate ethanol solution and 10 mL of a 3.5 mg / mL copper methanesulfonate ethanol solution were added.
[0169] Embodiment 10:
[0170] This example is substantially the same as Example 1, except that in step 4, 10 mL of 2.5 mg / mL copper (II) acetylacetonate ethanol solution and 10 mL of 3.5 mg / mL copper tetrafluoroborate ethanol solution were added.
[0171] Embodiment 11:
[0172] This embodiment is basically the same as embodiment 2, except that in step 1, only zinc acetate is used to form the metal salt precursor solution, and the zinc oxide nanoparticle ethanol solution is obtained in step 2. The zinc oxide ethanol solution used in step 3 is not the zinc oxide magnesium ethanol solution in embodiment 1, and the composite material formed is copper oxide-doped zinc oxide.
[0173] Embodiment 12:
[0174] This embodiment is basically the same as embodiment 2, except that: in step 1, aluminum acetate is used instead of magnesium acetate, and the zinc oxide aluminum nanoparticle ethanol solution is obtained in step 2. The zinc oxide aluminum ethanol solution used in step 3 is not the zinc oxide magnesium ethanol solution in embodiment 1, and the composite material formed is copper oxide-doped zinc oxide aluminum.
[0175] Embodiment 13:
[0176] This example is substantially the same as Example 1, except that in step 4, 10 mL of 6.0 mg / mL manganese trifluoromethanesulfonate ethanol solution is added instead of copper (II) trifluoromethanesulfonate.
[0177] Embodiment 14:
[0178] This example is substantially the same as Example 1, except that in step 4, 10 mL of 6.0 mg / mL chromium methanesulfonate ethanol solution is added instead of copper (II) trifluoromethanesulfonate.
[0179] Embodiment 15:
[0180] This example is substantially the same as Example 1, except that in step 4, 10 mL of 1.5 mg / mL copper (II) trifluoromethanesulfonate ethanol solution is added.
[0181] Embodiment 16:
[0182] This example is substantially the same as Example 1, except that in step 4, 10 mL of 12 mg / mL copper (II) trifluoromethanesulfonate ethanol solution is added.
[0183] Comparative Example 1:
[0184] This embodiment is basically the same as embodiment 1, except that step 3 and subsequent steps are not performed, and zinc magnesium oxide nanoparticles are obtained in step 2.
[0185] Comparative Example 2:
[0186] This embodiment is basically the same as embodiment 1, except that: Step 3 and Step 4 are as follows: 50 mL of the 60 mg / mL zinc oxide and magnesium oxide ethanol solution is taken, and 1 mL of the 5.0 mg / mL copper oxide ethanol solution is added. The mixed solution is stirred for 6 hours, and then the solution is washed three times by precipitation in excess ethyl acetate or acetone to obtain a zinc oxide and magnesium oxide-copper oxide mixed material.
[0187] Among them, synthesis of copper oxide: add an appropriate amount of copper chloride to 30 mL of ethanol to prepare a copper chloride ethanol solution with a total concentration of 1 M, wherein 0.015 mmol of sodium citrate is added to obtain a mixed solution A. Weigh an appropriate amount of sodium hydroxide and dissolve it in 5 ml of ethanol solution to obtain an alkali solution; add the alkali solution to the mixed solution A at a molar ratio of OH- to copper ions of 1.8:1 to form a mixed solution with a pH of 13, and then stir at 80°C for 1 hour to obtain a copper oxide nanoparticle solution. Filter the reaction product, centrifuge and wash it to obtain copper oxide.
[0188] Device Example 1
[0189] The device embodiment provides a quantum dot light emitting diode and a method for preparing the same, which specifically includes the following steps.
[0190] Step 1: Place the ITO glass sheet in a glass dish filled with ethanol solution, and ultrasonicate with acetone, deionized water, and ethanol for 20 minutes respectively, and then blow dry with a nitrogen gun; then place the cleaned ITO glass sheet in oxygen plasma for further cleaning for 10 minutes; continue to use UV-ozone to treat the surface of the ITO substrate for 15 minutes;
[0191] Step 2: Spin-coat the cleaned ITO glass sheet with PEDOT:PSS (thickness of about 25 nm) in air at a speed of 3500 r / min for 30 seconds; after spin coating, place it in air for annealing at 150°C for 30 minutes to obtain a hole injection layer; after annealing, quickly transfer the sheet to a glove box in a nitrogen atmosphere;
[0192] Step 3: Continue to spin-coat TFB (8 mg / mL, chlorobenzene solution) on the glass / ITO / PEDOT:PSS device at a speed of 3000 r / min for 30 seconds; after the spin coating is completed, anneal in a glove box at a temperature of 180°C for 30 minutes to obtain a hole transport layer with a thickness of 30 nm;
[0193] Step 4: Spin-coat Cd0.1ZnSe / Cd0.4Zn0.6Se / ZnSe / ZnS green quantum dots on the hole transport layer at a spin-coating speed of 2000 r / min for 30 seconds; after spin-coating, anneal at 60 degrees Celsius in a glove box for 5 minutes to obtain a light-emitting layer;
[0194] Step 5: The composite material in Example 1 is formed into a composite material ethanol solution with a concentration of 30 mg / mL, and spin-coated on the light-emitting layer at a speed of 3000 r / min for 30 seconds, and dried to obtain an electron transport layer with a thickness of 30 nm.
[0195] Step 6: Place the sample prepared in step 5 into a vacuum chamber, evaporate a top silver electrode with a thickness of 100 nm, and encapsulate.
[0196] Device Examples 2-16
[0197] This device embodiment is basically the same as device embodiment 1, and the only difference is that in step 5, the composite materials of embodiments 2-16 are used respectively.
[0198] Device Comparison Example 1-2
[0199] The device embodiments 1-2 are basically the same as the device embodiment 1, and the only difference is that the zinc oxide magnesium-ethanol solution in comparative example 1 is directly used in step 5, and the zinc oxide magnesium-copper oxide mixed material in comparative example 2 is used in step 5.
[0200] Test 1:
[0201] In the process of preparing the quantum dot light-emitting diodes of device example 2 and device comparative example 1, after preparing the electron transport layer, an AFM (atomic force microscope) roughness test was performed on the electron transport layer, and the roughness of the electron transport layer was obtained. Figure 5 and Figure 6 , Figure 5 and Figure 6 The AFM images of the electron transport layer in device comparative example 1 and device embodiment 2 respectively correspond to each other.
[0202] Depend on Figure 5 and Figure 6 It can be seen that the arithmetic mean roughness (Ra) and root mean square roughness (Rq) of the electron transport layer in device embodiment 2 are much smaller than those in device comparative example 1, indicating that the electron transport layer formed by the composite material provided in the present application has good film-forming property and surface uniformity. The composite material provided has good film-forming property, which may be due to the fact that the anions in the first metal salt are connected to the surface of the n-type metal oxide, and can react with a large number of oxygen defects (O 2 + ) and effectively reduce the aggregation and regrowth of zinc oxide and magnesium particles, thereby improving the film-forming property of the composite material. It is also possible that during the preparation of the composite material, the holes (h+) generated by photocatalysis can effectively fill the defects (such as oxygen vacancies, etc.) on the surface of the n-type metal oxide, play a role in passivating the n-type metal oxide, and can effectively avoid the regrowth of n-type metal oxide nanoparticles, improve the uniformity of the particles in the composite material, reduce agglomeration, and thus also improve the film-forming property of the composite material.
[0203] Test 2:
[0204] The zinc oxide magnesium-ethanol solution of Comparative Example 1 and the composite material-ethanol solution of Example 2 were tested for hydrated particle size using a laser particle size analyzer to obtain a hydrated particle size distribution diagram. Figure 7 and Figure 8 The hydrated particle size distribution diagrams correspond to those of Example 1 and Example 2, respectively.
[0205] Depend on Figure 7 and Figure 8It can be seen that the average particle size of nano zinc oxide and magnesium in Comparative Example 1 is 4.62 nm, and the average particle size of the composite material formed in Example 2 is 3.21 nm, and the particle size distribution is more concentrated and the particle size distribution is more uniform. It may be that in the process of photocatalytic in-situ generation of copper oxide to obtain the composite material, the holes generated by photocatalysis can effectively fill the defects on the surface of the zinc oxide and magnesium material (such as oxygen vacancies, etc.), play a role in passivating the zinc oxide and magnesium material, and the organic groups are connected to the surface of the zinc oxide and magnesium material, effectively avoiding the regrowth of zinc oxide and magnesium nanoparticles and reducing agglomeration, resulting in smaller particles of the composite material and more uniform distribution, thereby improving the film-forming property of the composite material.
[0206] Test 3:
[0207] The quantum dot light-emitting diodes of device examples 1-14 and device comparison examples 1-2 were tested for life span, and the data are shown in Table 1.
[0208] The test method for the lifespan T95@1000nit is: the time required for the device to reduce its brightness to a certain percentage of the maximum brightness under constant current or voltage drive. The time when the brightness drops to 95% of the maximum brightness is defined as T95, and this lifespan is the measured lifespan. In order to shorten the test cycle, the device lifespan test is usually carried out at high brightness by accelerating device aging, and the lifespan at high brightness is obtained by fitting the extended exponential decay brightness attenuation fitting formula. For example, the lifespan at 1000nit is calculated as T95@1000nit. The specific calculation formula is as follows:
[0209]
[0210] Among them, T95 L For lifespan at low brightness, T95 H is the measured lifetime under high brightness, L H To accelerate the device to the highest brightness, L L is 1000nit, A is the acceleration factor, and this experiment measured the lifespan of several groups of green QLED devices at rated brightness and found that the A value was 1.7.
[0211] Test 4:
[0212] The single electron devices (EOD) corresponding to device embodiments 1-16 and device comparative examples 1-2 were tested for electron injection performance, and the data of the corresponding EOD device current density and EOD device operating voltage are shown in Table 1. Figure 9a and Figure 9b JV curves (i.e., current density-voltage curves) of single electron devices corresponding to device embodiments 1-16 and device comparative examples 1-2, Fig.10a and 10b1-16 and 1-2 are operating voltage curves of single-electron devices corresponding to device embodiments 1-16 and device comparison examples 1-2.
[0213] Among them, the preparation method of the single electron device (EOD) is basically the same as the preparation method of the corresponding complete QLED device. The only difference is that after subtracting the hole injection layer and the hole transport layer, the device structure is: glass substrate / ITO / QD light-emitting layer / electron transport layer / Ag electrode.
[0214] The electron injection performance test method is: control QE PRO and Keithley 2400 through LabView to build a QLED efficiency test system. The system tests the current density-voltage curve of the single carrier transport thin film device (EOD). The current density under the working voltage (8V) of the device is compared with the working voltage in the stable state. The working voltage in the stable state refers to the working voltage of the device in the device balance stage when the device runs for more than 4 hours during the device life test.
[0215] Table 1
[0216]
[0217]
[0218] It can be seen from Table 1 and Figures 9-10 that, relative to device comparison examples 1 and 2, the EOD device current density (at 8V) corresponding to device embodiments 1-16 all showed a decrease, the EOD device operating voltage of each embodiment also showed an increase, and the life of the device was also significantly improved. This shows that the composite material of the present application is used to prepare an electron transport layer, which can improve the carrier balance by reducing electron injection, thereby achieving the purpose of improving life. At the same time, it also shows that the copper oxide-doped zinc magnesium oxide prepared by the composite material preparation method of the present application, compared with the simple direct mixing of zinc magnesium oxide and copper oxide and relying only on electrostatic force to combine, can more effectively reduce the electron injection of the QLED device, thereby improving the life of the device.
[0219] It can be seen from device embodiments 1-3 and 15-16 that the electron injection inhibition or reduction effect of device embodiments 15 and 16 is relatively small. This may be because a small amount of organic copper salt is added, resulting in a small amount of copper oxide contained in the composite material, and thus the reduction and inhibition effect on electron injection is relatively small; while adding more organic copper salt leads to a larger amount of copper oxide contained in the composite material, which hinders electron injection too much, resulting in a significant decrease in the current density of the EOD device and a significant increase in the operating voltage, and the life of the light-emitting diode device shows a decreasing trend.
[0220] Test 5:
[0221] The conduction band positions of zinc magnesium oxide in Example 1 and copper oxide prepared in Comparative Example 2 were measured by Mott-Schottky. Specifically, the test was conducted on a Zennium E electrochemical workstation (zhner, Germany) at a test frequency of 500 Hz, 1 kHz, and 1.5 kHz (three frequencies to improve accuracy), an amplitude of 10 mV, and a standard three-electrode quartz cell containing a 0.5 M Na2SO4 electrolyte solution, a platinum wire as a counter electrode, and Hg / Hg in saturated KCl. 2+ As a reference electrode, an ITO glass substrate was pre-coated with a test sample film (coating area of 1 cm 2 , the thin film preparation method is the same as the device film preparation method) as the working electrode. Fig.11 and Fig.12 Conduction band position diagrams of zinc magnesium oxide (ZMO) and cobalt oxide, respectively.
[0222] Combination Fig.11 and Fig.12 It can be seen that the conduction band position of ZMO is at -0.28eV, and the conduction band position of copper oxide is at -0.36eV. The composite material formed by copper oxide is in situ generated in zinc magnesium oxide. By introducing copper oxide with a higher energy level between zinc magnesium oxide and the cathode electrode, an electron barrier is formed between zinc magnesium oxide and the cathode electrode, thereby reducing the electron injection of the device and improving the carrier balance and life of the device.
[0223] The composite materials and their preparation methods, light-emitting devices and their preparation methods, and display devices provided in the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the methods and core ideas of the present application. At the same time, for technical personnel in this field, according to the ideas of the present application, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A method for preparing a composite material, characterized in that: include: Providing a first mixture, wherein the first mixture includes an n-type metal oxide and a solvent; After subjecting the first mixture to a first light treatment, adding a first metal salt to the first mixture, and continuing to subject the first mixture to a second light treatment to obtain a composite material; The solvent contains a hole sacrificial agent, and the conduction band energy level of the first metal oxide prepared from the first metal salt is 0.2 to 0.5 eV higher than the conduction band energy level of the n-type metal oxide.
2. The preparation method according to claim 1, characterized in that The n-type metal oxide includes a doped or undoped second metal oxide, the doped second metal oxide includes the undoped second metal oxide and a doping element, the undoped second metal oxide includes one or more of zinc oxide, titanium dioxide, and tin dioxide, and the doping element includes one or more of Mg, Ca, Li, Ga, Al, Co, Zr, W, Ti, and Y; and / or, the solvent comprises one or more of water, alcohol solvents, ether solvents, tetrahydrofuran, acetone, chlorobenzene, toluene, and dimethyl sulfoxide; And / or, the hole sacrificial agent includes one or more of acetonitrile, triethylamine, triethanolamine, sodium sulfite, methanol, ethanol, and lactic acid; And / or, the first metal salt comprises an anion and a first metal cation, and the anion is selected from one or more of the following structural formulas: wherein each occurrence of R1, R2, R3, and R4 is independently selected from one or more of H, D, -NH2, C1-C30 alkyl, aryl having 5-30 ring atoms, heteroaryl having 5-30 ring atoms, and C1-C30 alkyl substituted with at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, aryl having 5-30 ring atoms substituted with at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, and heteroaryl having 5-30 ring atoms substituted with at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, and X is halogen; and / or, the mass ratio of the first metal salt to the n-type metal oxide is (1-2):20; And / or, the concentration of the n-type metal oxide in the first mixture is 35-60 mg / mL.
3. The preparation method according to claim 2, characterized in that: Each occurrence of R1, R2, R3, and R4 is independently selected from -NH2, C1-C10 alkyl, C1-C10 alkyl substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, and aryl having 5 to 24 ring atoms substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl; And / or, the first metal cation includes one or more of copper ions, manganese ions, and chromium ions.
4. The preparation method according to claim 2 or 3, characterized in that: The anion includes one or more of the following structural formulas:
5. The preparation method according to claim 1, characterized in that: The first light treatment adopts full spectrum irradiation; And / or, the first light treatment lasts for 1 to 2 hours; and / or, during the first light treatment of the first mixture, the temperature of the first mixture is maintained at 0-30° C.; and / or, during the first light irradiation process, the first mixture is in a stirring state; And / or, the second light treatment uses full spectrum irradiation; And / or, the second light treatment time is 4 to 10 hours; And / or, after adding the first metal salt to the first mixture, a second mixture is obtained, and during the second light treatment of the second mixture, the temperature of the second mixture is maintained at 0-30° C. and the second mixture is in a stirring state.
6. A composite material, characterized in that: Prepared by the preparation method of the composite material according to any one of claims 1 to 5; and / or, the composite material comprises an n-type metal oxide doped with a first transition metal oxide, wherein the conduction band energy level of the first transition metal oxide is 0.2 to 0.5 eV higher than the conduction band energy level of the n-type metal oxide; Wherein, the surface of the n-type metal oxide is connected with a negatively charged group, and the group is selected from one or more of the following structural formulas: Each occurrence of R1, R2, R3, and R4 is independently selected from one or more of H, D, -NH2, C1-C30 alkyl, aryl having 5-30 ring atoms, heteroaryl having 5-30 ring atoms, and C1-C30 alkyl substituted with at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, aryl having 5-30 ring atoms substituted with at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, and heteroaryl having 5-30 ring atoms substituted with at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, and X is halogen.
7. The composite material according to claim 6, characterized in that The n-type metal oxide includes a doped or undoped second metal oxide, the doped second metal oxide includes the undoped second metal oxide and a doping element, the undoped second metal oxide includes one or more of zinc oxide, titanium dioxide, and tin dioxide, and the doping element includes one or more of Mg, Ca, Li, Ga, Al, Co, Zr, W, Ti, and Y; And / or, the first metal oxide includes one or more of copper oxide, manganese oxide, and chromium oxide; and / or, the average particle size of the n-type metal oxide is 3 to 10 nm; and / or, the average particle size of the first metal oxide is 2 to 5 nm; And / or, the mass ratio of the first metal oxide to the n-type metal oxide is (3-8):
100.
8. A light emitting device, characterized in that: include: A first electrode and a second electrode arranged opposite to each other; A light-emitting layer is disposed between the first electrode and the second electrode; An electronic functional layer, disposed between the second electrode and the light-emitting layer; Wherein, the material of the electronic functional layer includes a composite material prepared by the method for preparing a composite material as described in any one of claims 1 to 5, or includes a composite material as described in any one of claims 6 to 7.
9. The light emitting device according to claim 8, characterized in that: The material of the light-emitting layer is selected from organic light-emitting materials or quantum dot light-emitting materials; the organic light-emitting material is selected from at least one of diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives or fluorene derivatives, TBPe fluorescent materials emitting blue light, TTPA fluorescent materials emitting green light, TBRb fluorescent materials emitting orange light and DBP fluorescent materials emitting red light; the quantum dot light-emitting material is selected from at least one of single-structure quantum dots, core-shell structure quantum dots and perovskite semiconductor materials, the single-structure quantum dots are selected from at least one of II-VI compounds, IV-VI compounds, III-V compounds and I-III-VI compounds, the II - Group VI compounds are selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS , CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZn The IV-VI group compound is selected from at least one of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe, and the III-V group compound is selected from at least one of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, at least one of GaPAs, GaPSb, AlNPs, AlNAs, AlNSb, AlPAs, AlPSb, InNPs, InNAs, InNSb, InPAs, InPSb, GaAlNPs, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNPs, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNPs, InAlNAs, InAlNSb, InAlPAs and InAlPSb, and the Group I-III-VI compound is at least one of CuInS, CuInSe and AgInS;The core of the quantum dots of the core-shell structure is selected from any one of the above-mentioned single-structure quantum dots, and the shell material of the quantum dots of the core-shell structure is selected from at least one of CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS and ZnS; the perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductors, or organic-inorganic hybrid perovskite semiconductors; the general structural formula of the inorganic perovskite semiconductor is AMX3, wherein A is Cs; + ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2 + Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl-, Br - , I- at least one; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2 + 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl-, Br - ,I - At least one of; And / or, the first electrode and the second electrode are independently selected from metal electrodes, carbon electrodes, doped or undoped metal oxide electrodes and composite electrodes; wherein the material of the metal electrode is selected from at least one of Al, Ag, Cu, Mo, Au, Ba, Ca, Ni, Ir and Mg; the material of the carbon electrode is selected from at least one of graphite, carbon nanotubes, graphene and carbon fiber; the material of the doped or undoped metal oxide electrode is selected from ITO, FTO, ATO, AZO, GZO, IZO , MZO, ITZO, ICO, AMO, SnO2, In2O3, Cd:ZnO, Ga:SnO2; the material of the composite electrode is selected from AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS and ZnS / Al / ZnS; And / or, the light-emitting device further comprises a hole functional layer, the hole functional layer is arranged between the first electrode and the light-emitting layer, and the hole functional layer comprises a hole injection layer and / or a hole transport layer; wherein the material of the hole transport layer is selected from arylamine, polyaniline, polypyrrole, poly(p-)phenylene vinylene and its derivatives, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compound, N,N,N',N'-tetraarylbenzidine, PEDOT:PSS and its derivatives, poly(N-vinylcarbazole) and its derivatives, polymethacrylate and its derivatives, poly(9,9 -octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, doped or undoped NiO, MoO3, WO3, V2O5, CrO3, CuO, MoS2, MoSe2, WS3, WSe3, CuS, CuSCN or one or more thereof; wherein the aromatic amine is selected from 4,4'-bis(9-carbazole)biphenyl, poly(9,9-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine), poly(N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl)diphenylamine), N,N'-bis(4-(N,N'-diphenyl-amino) triphenylamine, 4,4',4"-tri(carbazol-9-yl)triphenylamine, 4,4',4"-tri(N-carbazolyl)triphenylamine, 4,4',4"-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine, N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4'-diamine, -diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine, Spiro-NPB, Spiro-TPD, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro, Spiro-NPB; the poly(p-)phenylene vinylene and its derivatives are selected from one or more of poly(phenylene vinylene), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene] and poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene];The material of the hole injection layer is selected from poly(ethylenedioxythiophene): polystyrene sulfonate, 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanoquinone-dimethane, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, copper phthalocyanine, poly(9,9-dioctyl-fluorene-co-N-(4-butylphenyl)-diphenylamine), polyarylamine, poly(N-vinylcarbazole), polyaniline, polypyrrole, N,N,N',N'-tetrakis(4-methoxyphenyl)-benzidine, 4-bis[N-(1-naphthyl)-N-phenyl-amino]biphenyl, 4,4',4"-tris[phenyl(m-tolyl)amino]triphenylamine, 4,4' ,4"-tri(N-carbazolyl)-triphenylamine (TCTA), 1,1-bis[(di-4-tolylamino)phenylcyclohexane, 4,4',4"-tri(diphenylamino)triphenylamine doped with F4-TCNQ, p-doped phthalocyanine, F4-TCNQ doped N,N'-diphenyl-N,N'-di(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, transition metal oxides, transition metal sulfur compounds; wherein the transition metal oxides include one or more of NiO, MoO2, WO3, and CuO; the metal sulfur compounds include one or more of MoS2, MoSe2, WS3, WSe3, and CuS.; 10. A display device, characterized in that: The light emitting device comprises the light emitting device as claimed in any one of claims 8 to 9.